Factors influencing the extent of the ethical codes: Evidence from Slovakia - Jana Kozáková; Mária Urbánová; Radovan Savov (Journal of Risk and Financial Management, 2021)
Even though formalization of ethical principles is a must in today's business, research and evidence in the Slovak conditions remain scarce. Yet, creating an ethical business climate and especially the formalization of ethics through codes of ethics incorporated in corporate standards is a particularly interesting phenomenon in the conditions of transit economies due to the significant role of multinationals in this process. Therefore, the purpose of this study was to examine main factors influencing the extent of ethical codes in 225 subsidiaries of multinational companies operating in Slovakia. The conducted questionnaire study containing items focused on area and extent of ethical code, number of employees, economic performance, regional and industrial scope, ownership structure, and nationality of executive director was used as a tool for data collection. Factor analysis was processed to identify the interdependencies between observed variables and to find the latent variables. Further, the Kruskal-Wallis test was applied to identify the differences among the variables along with the Bonferroni correction test, which specified the items between which the significant difference occurred. The following findings emerged. First, companies with lower extent of ethical code use general phrases. When they want to specialize on any ethics problems, extent must be wider. Second, companies with a lower number of employees do not need extensive ethical code due to clear rules with which they are familiar in a direct way by owners. In multinational companies, the communication of ethical rules is realized via ethical codes with specific purposes because the direct way is impossible. Third, companies with foreign ownership used different managerial approaches, and therefore ethical codes differ in extent and content.
Keywords: 330; corporate code of ethics; extent of code; content of ethical code; ownership structure; company size